The effect of reality therapy group counseling with the WDEP technique on increasing student academic resilience - Afifah, Hasna Nur; Purwati, Purwati; Putro, Hijrah Eko (Universitas Islam Negeri Raden Intan Lampung, 2022)
As a student, many demands are imposed, starting from the needs of academic and non-academic values, participating in various intra and extracurricular activities to add value and expertise, fibre and much more. From the many demands that exist, students often experience academic stress. For this reason, high academic resilience is needed to cope with academic stress. The purpose of this study was to examine the effect of group counselling with the WDEP technique to improve students' academic resilience. This WDEP technique is one of the techniques in reality therapy which is an acronym for Want, Doing and Direction, Evaluation and Planning. The research was conducted on grade VII G students at SMP Negeri 3 Magelang. Pre-experiment, using one group pre-test post-test design. Where the design uses one group that will be used as an experimental group to be given treatment in the form of WDEP technique group counselling services. By using a purposive sampling technique, from 32 students in the class, 8 students were taken as members of the experimental group to participate in group counselling activities. Meanwhile, the method for analyzing the data used parametric statistics paired sample t-test with SPSS 25 software. The results of the study show that the WDEP technique of group counselling affects increasing students' academic resilience.